2002
DOI: 10.17221/4849-pps
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the cluster of wheat rust resistance genes Yr17, Lr37, and Sr38 by a molecular marker

Abstract: AMBROZKOVÁ M., DEDRYVER F., DUMALASOVÁ V., HANZALOVÁ A., BARTOŠ P. (2002): Determination of the cluster of wheat rust resistance genes Yr17, Lr37, and Sr38 by a molecular marker. Plant Protect. Sci., 38: 41-45.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…For the three QTL detected in this study, the parent carrying the resistance allele is the cultivar Renan. Renan carries known resistance genes to a number of diseases, including rust resistance genes Yr17 , Lr37 , and Sr38 , all originating from a chromosomal introgression from Aegilops ventricosa on wheat chromosome 2AS [ 88 , 89 , 90 ], eyespot resistance gene Pch1 on chromosome 7D [ 91 , 92 ], and powdery mildew resistance gene Pm4b on chromosome 2AL [ 91 , 93 ]. None of these known resistances to other diseases colocalize with the three QTL detected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For the three QTL detected in this study, the parent carrying the resistance allele is the cultivar Renan. Renan carries known resistance genes to a number of diseases, including rust resistance genes Yr17 , Lr37 , and Sr38 , all originating from a chromosomal introgression from Aegilops ventricosa on wheat chromosome 2AS [ 88 , 89 , 90 ], eyespot resistance gene Pch1 on chromosome 7D [ 91 , 92 ], and powdery mildew resistance gene Pm4b on chromosome 2AL [ 91 , 93 ]. None of these known resistances to other diseases colocalize with the three QTL detected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Тем не менее необходимо уточнить, что ген Lr37 характеризуется в основном как возрастной (устойчивость к патогену экспрессируется со стадии флаг-листа), редко проявляет IT = 1,2 -N в стадии проростков, при этом наблюдается температурочувствительность (большая экспрессия при температуре 17 °С) (Bariana, McIntosh., 1993). По данным ряда авторов, ген Lr37 в стадии проростков устойчив лишь к некоторым редким патотипам P. triticina (Ambrozova et al, 2002). Ген Lr19 -ювенильный, температурочув-ствительность отсутствует (McIntosh et al, 1995).…”
Section: результаты и обсуждениеunclassified
“…In the case of crops, key events determining the properties of the current varieties include domestication [ 25 , 26 , 27 , 28 ], and in the second half of the last century, the advent of modern breeding, which typically aims at developing high-yield cultivars able to value farming inputs, i.e., under conditions close to the agronomic optimum [ 29 , 30 , 31 ]. Modern cultivars may differ from ancient plant genotypes in terms of their root exudation because of differences in the physiology and metabolic composition of their plant tissues [ 32 , 33 , 34 ], root architecture [ 32 , 35 , 36 ] and disease resistance [ 37 , 38 , 39 ], which might lead to particular rhizobacterial community composition [ 17 , 21 , 40 , 41 , 42 , 43 ]. Indeed, interaction analysis of 192 bread wheat accessions with the 2,4-diacetylphloroglucinol (DAPG)-producing PGPR Pseudomonas ogarae F113 showed that the abilities for PGPR root colonization and expression of the DAPG genes phl on roots were higher overall in ancient wheat genotypes than modern genotypes, even though the capacity for PGPR interaction was maintained in certain modern cultivars [ 44 ].…”
Section: Introductionmentioning
confidence: 99%